2016
DOI: 10.1016/j.jcin.2016.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Both Early Reperfusion and Therapeutic Hypothermia in Limiting Myocardial Infarct Size Post–Cardiac Arrest in a Porcine Model

Abstract: Abstract:Background: Cohort studies have shown that one in four post cardiac arrest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…In addition, it could have been shown that TTM alone without reperfusion reveals adverse effects because the extent of myocardial infarction was comparable independently of treatment with TTM. TTM plus reperfusion resulted in the best recovery of cardiac function with the lowest myocardial infarction size [39]. This experimental evidence confirms the disadvantage of delayed coronary revascularization and limits the benefit of sole TTM after cardiac arrest.…”
Section: Targeted Temperature Managementsupporting
confidence: 55%
“…In addition, it could have been shown that TTM alone without reperfusion reveals adverse effects because the extent of myocardial infarction was comparable independently of treatment with TTM. TTM plus reperfusion resulted in the best recovery of cardiac function with the lowest myocardial infarction size [39]. This experimental evidence confirms the disadvantage of delayed coronary revascularization and limits the benefit of sole TTM after cardiac arrest.…”
Section: Targeted Temperature Managementsupporting
confidence: 55%
“…Translational models of AMI have a major importance to develop interventions for the clinical practice [18, 51, 52]. For this purpose, pigs are excellent model animals, since their cardiac anatomy and cardiovascular physiology exhibit similarities to the human heart [53].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in biomarkers of STEMI, especially specific Hs‐troponin T, indicates a down‐regulation of the injury related to ischemia/reperfusion . The effective reduction of Troponin T levels following treatment with TH was in accordance with a 75% reduction in IS in STEMI models. In the present study, intracoronary hypothermia caused a significant reduction in Hs‐troponin T concentrations post‐PPCI procedure, which was in agreement with Gotberg et al who reported that total body hypothermia caused a significant decrease in troponin T. However, Erlinge et al could not find the same decrease in troponin T with augmentation of sample size.…”
Section: Discussionmentioning
confidence: 60%